2008
DOI: 10.1007/s10201-007-0232-2
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition process of organic matter derived from freshwater phytoplankton

Abstract: We investigated the biodegradation process of freshwater phytoplanktonic organic matter using incubation experiments, with special reference to changes in three major biomolecules: neutral aldoses, amino acids and fatty acids. The concentration of neutral aldoses decreased drastically relative to amino acids and fatty acids during the early decomposition phase (days 0-7), owing largely to the rapid decomposition of storage carbohydrate. This resulted in a temporary decrease in the C/N ratio of organic matter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Additionally, the decomposition rates of different carbohydrate components are also an important parameter in such a discussion. Several authors have demonstrated that glucose, mannose and xylose, the main carbohydrate components in Merin lagoon in this period, could be quickly degraded, decreasing the residence time of these components during intense heterotrophic bacterial metabolism (Giroldo et al, 2003(Giroldo et al, , 2005bHanamachi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the decomposition rates of different carbohydrate components are also an important parameter in such a discussion. Several authors have demonstrated that glucose, mannose and xylose, the main carbohydrate components in Merin lagoon in this period, could be quickly degraded, decreasing the residence time of these components during intense heterotrophic bacterial metabolism (Giroldo et al, 2003(Giroldo et al, , 2005bHanamachi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular polysaccharides production by phytoplankton depends on the species, their physiological state and environmental conditions (Urbani et al, 2005;Hanamachi et al, 2008). As a consequence, this process promotes qualitative and quantitative variations in the dissolved organic carbon (DOC) pool in the planktonic environment depending on the abundant species of primary producers and heterotrophic organisms (DellamanoOliveira et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…DOM represents a complex of compounds and derives from main sources: allochthonous material produced from degradation of humic substances coming from runoff of terrestrial origin (Kieber et al, 2006;Miller et al, 2009); and autochthonous material, produced by autotrophic and heterotrophic in situ activities, but mainly by the bacterial degradation of phytoplankton and macrophytes (Kritzberg et al, 2004;Hanamachi et al, 2008;Henderson et al, 2008;Guillenette and Del Giorgio, 2012). The two different sources of DOM can be distinguished from differences in their optical and chemical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasm and the exudates of these plants comprise the main source of labile organic carbon (Peret and Bianchini Jr., 2004;Hanamachi et al, 2008). The supporting tissues of macrophytes are a significant source of refractory carbon (i.e.…”
Section: Introductionmentioning
confidence: 99%